2014
DOI: 10.1002/chem.201405229
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Radical Carbofluorination of Non‐activated Alkenes

Abstract: The Meerwein arylation has recently become an even more powerful tool for the functionalization of alkenes. Besides the attachment of an aryl group, radical reactions of this type allow the introduction of several different heteroatoms and a broad variety of alkenes are meanwhile tolerated as substrates. Closing a long-standing gap of the methodology, this communication describes the first intermolecular Meerwein-type carbofluorination. In metal-free reactions, arylalkyl fluorides were obtained from arylhydraz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 88 publications
0
24
0
Order By: Relevance
“…[6c,m,7] As omewhat less developed but very challenging area involves carbofluorination reactions for the synthesis of fluorinecontaining isocyclic compounds. [8] Al imited number of reports have also been published on intermolecular aminofluorination [9] and carbofluorination [10] reactions. Relatively few studies have been reported for the application of the same reagent under similar reaction conditions to perform all three types of cyclization reactions.…”
mentioning
confidence: 99%
“…[6c,m,7] As omewhat less developed but very challenging area involves carbofluorination reactions for the synthesis of fluorinecontaining isocyclic compounds. [8] Al imited number of reports have also been published on intermolecular aminofluorination [9] and carbofluorination [10] reactions. Relatively few studies have been reported for the application of the same reagent under similar reaction conditions to perform all three types of cyclization reactions.…”
mentioning
confidence: 99%
“…Yields after purification by column chromatography. Yields in brackets refer to reactions without anisole …”
Section: Resultsmentioning
confidence: 99%
“…Our deeper interest in this topic arose from a recently developed alkene functionalization (Scheme B) . Starting from phenylhydrazines 5 and alkenes 6 , the first Meerwein‐type carbofluorination could be put into practice, in which the desired arylation products 7 were obtained by trapping of alkyl radical 8 by Selectfluor ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…By judiciously integrating ease of carbon radical generation, through either transition‐metal catalysis or photocatalysis, with productive fluorination techniques, considerable progress has been attained in the arena of fluoroalkylation reactions, although most of the reported methods still show a heavy reliance on electrophilic fluorination reagents . However, the fluoroarylation counterpart is comparatively underdeveloped, probably due to a relative lack of efficient avenues for the easy production of aryl radical intermediates …”
Section: Methodsmentioning
confidence: 99%